France : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that in a context of weakening economic conditions in Europe and sizeable fiscal consolidation and domestic policy uncertainty, the French economy flat lined in 2012. However, recent improvements in economic indicators support the expectation of a gradual recovery in the second half of 2013. Credit conditions remain supportive, and private demand is unencumbered by balance sheet repair issues and thus more apt to respond favorably to an improvement in confidence. The economy is projected to contract by 0.2 percent in 2013 and to grow by 0.8 percent in 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: National Government Expenditures and Related Policies